Taxing Sugar-sweetened Beverages in Latin America: A Qualitative Comparative Examination of the Mexican and Chilean Experience (P22-009-19). (13th June 2019) - Fuster, Melissa; Burrowes, Sahai; Lewis, Sarah; McCarthy, Benjamin; Shen, Gordon
Abstract: Objectives: Mexico and Chile implemented sugar-sweetened beverage (SSB) taxes in 2014. This study aimed to trace and compare the SSB tax policy process, and examine the role and perspectives of outside government stakeholders in the process. Methods: Qualitative study design using key informant (KI) interviews and document review. We interviewed 24 KIs involved in the SSB tax policy process (16 researchers, 5 civil society organizations (CSOs), and 3 food and beverage industries, F&BI) to examine perceptions on the tax process, effectiveness and future. Two independent coders analyzed the transcripts, using emergent and a priori codes. The results were triangulated with a document review, including research and newspaper articles, and reports covering the pre- and post-tax periods ( n = 347). Results: In Mexico, the tax on beverages with added sugars (1 peso/liter, or a 10% tax) stemmed from a longer process, compared to Chile, where the tax resulted from a pre-existing one applied to beverages with more than 6.25 g of sugar/100 ml (increased from 13 to 18%). In both countries, CSOs and the F&BI had direct influence on policy makers. CSOs were key in facing F&BI opposition before and after implementation. Researchers' influence was indirect, providing evidence for or against the tax. There was agreement that the SSB tax alone was insufficient to address noncommunicable diet-related chronic diseases (NDCs). KIs noted needed tax improvements (e.g., increasing the rate, modifying the tax basis, and using revenue for public health initiatives). KIs against the tax argued for nutrition education as a better option to change SSB demand to encourage F&BI product reformulation. The results will examine the taxes within other public health initiatives in the countries and political considerations. Conclusions: While often touted as nutrition policy win, SSB taxes are one part of a larger nutrition policy toolbox. The study contributes to past research examining the Chilean and Mexican taxes, individually and mostly through quantitative methods. The comparative perspective shows different potential paths to tackling NDCs through policy, while facing F&BI pushback, and lessons for other countries seeking to implement SSB taxes at a national level. Funding Sources: The research was funded by PSC-CUNY Research Award 60, 806–00 48.